O perfil da antiestreptolisina O no diagnóstico da febre reumática aguda - Machado, Claudia Saad Magalhães [UNESP]; Ortiz, Katya; Martins, Alessandra De Lourenço Budin; Martins, Roberto Salvador; Machado, Nilton Carlos [UNESP] (Sociedade Brasileira de Pediatria, 2001)
OBJECTIVE: to determine ASO titer profile by establishing ARF differential diagnoses of other diseases with high levels of ASO antibodies. METHODS: we investigated 78 patients with ARF at onset and follow-up, 22 with isolated chorea at onset, 45 with recurrent oropharyngeal tonsillitis, and 23 with recent flare of juvenile idiopathic arthritis. We tested ASO with automated particle-enhanced immunonephelometric assay (Behring®-Germany). The ASO (IU/ml) titers were assessed at the following time intervals: 0-7 days, 1-2 weeks, 2-4 weeks, 1-2 months, 2-4 months, 4-6 months, 6-12 months, 1-2 years, 2-3 years, 3-4 years, and 4-5 years after onset of ARF. RESULTS: ASO titers in patients diagnosed with ARF had a significant increase up to the 2-4-month time interval (P < 0.0001). Baseline levels were observed afterwards in patients under regular penicillin prophylaxis. The levels of ASO in ARF were also significantly higher than in patients with isolated chorea, recurrent oropharyngeal infections or juvenile idiopathic arthritis (P = 0.0025), when age-matched samples of these groups were compared. The test’s sensitivity was 73.3% and the specificity was 57.6%, and it was calculated taking into account the upper limit of normality at 320 IU/ml, as well as the established diagnosis of ARF. The test’s specificity and positive predictive value increased with rising or higher titers, being higher with titers above 960 UI/ml. CONCLUSION: this reappraisal of ASO profile in ARF patients indicates a remarkable response during the acute phase, and that points to the extent to which ASO levels may differentiate ARF from other diseases with high levels of ASO antibodies, as coincidental but unrelated streptococcal infection or chronic arthritis flareup.

OBJETIVO: estabelecer o perfil dos títulos de ASO, mediante o diagnóstico diferencial da FRA com outras afecções que também cursam com níveis elevados de ASO. MÉTODOS: foram estudados 78 casos de FRA na apresentação e seguimento, 22 de coréia isolada, 45 de infecções orofaringeanas recorrentes (IOR) e 23 de artrites idiopáticas juvenis (AIJ), com início ou reativação recente. A determinação seqüencial de ASO (UI/ml) foi realizada por ensaio nefelométrico automatizado (Behring®-Germany) nos períodos de 0-7 dias, 1-2 semanas, 2-4 semanas, 1-2 meses, 2-4 meses, 4-6 meses, 6-12 meses, 1-2 anos, 2-3 anos, 3-4 anos e 4-5 anos após o diagnóstico. RESULTADOS: os títulos de ASO na fase aguda da FRA apresentaram elevação significante até o intervalo de 2- 4 meses (p < 0,0001), quando atingiram os níveis basais e permaneceram estáveis por 5 anos na vigência de profilaxia secundária com penicilina. Os valores de ASO na apresentação da FRA também foram mais elevados e com diferença significante quando comparados aos de coréia isolada, IOR e AIJ (p = 0,0025). As variações etárias e o limite superior da normalidade (320 UI/ml) foram considerados para a comparação entre estes grupos, assim como para o cálculo da sensibilidade (73,3%) e da especificidade (57,6%) mediante o diagnóstico clínico de FRA. A especificidade e valor preditivo positivo do teste aumentaram com títulos crescentes, sendo mais alta com títulos > 960 UI/ml. CONCLUSÃO: esta reavaliação do perfil da ASO indicou uma resposta exuberante na fase aguda da febre reumática indicou ainda que os seus níveis séricos podem diferenciá-la de outras afecções que também cursam com níveis elevados de ASO, como as infecções orofaringeanas recorrentes ou as artrites idiopáticas juvenis em atividade.
Antistreptolysin O titer profile in acute rheumatic fever diagnosis
Keywords: arthritis; rheumatic fever; antistreptolysin; chorea; artrite; febre reumática; antiestreptolisina; coréia